Long-term follow-up after endoscopic resection of gastric superficial neoplastic lesions in Portugal - Pimentel-Nunes, Pedro; Mourão, Francisco; Veloso, Nuno; Afonso, Luís Pedro; Jácome, Manuel; Moreira-Dias, Luís; Dinis-Ribeiro, Mário (Endoscopy, 2014)
Background and study aims: Although endoscopic resection for the treatment of gastric superficial neoplastic lesions is an established first-line treatment in Eastern countries, its role has yet to be considered in Western guidelines, mostly due to a lack of long-term studies. The aim of this study was to describe long-term outcomes for endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) in the treatment of gastric neoplasias in Portugal.Patients and methods: This was a single-center, retrospective, cohort study between March 2003 and April 2013. A total of 162 consecutive patients with 195 gastric superficial neoplasias underwent EMR (n = 54) or ESD (n = 141) and were followed up for a median of 3.2 years.Results: Resection was feasible in 97 %, with en bloc and R0 resection rates of 85 % (94 % ESD vs. 61 % EMR; P = 0.001) and 81 % (91 % ESD vs. 54 % EMR; P < 0.001), respectively. The recurrence rate was 7 %, and recurrence was associated with Rx/R1 resection irrespective of resection technique (OR 5.8; 95 % confidence interval 3.9 – 8.8). The long-term curative resection rate was 86 % after one procedure and 91 % after two procedures. Adverse events were observed in 13 % of cases: 8 % bleeding and 2 % of perforations (EMR = ESD). Surgery was performed in 7 %: 6 % after noncurative endoscopic resection and 1 % due to complications. Metachronous lesion detection rate was 1 % – 1.5 % per patient year. Cancer-specific survival rate was 100 % at follow-up.Conclusions: For the first time in a Western country, results are reported to be similar to those in Eastern countries. Endoscopic resection, particularly ESD, is a highly effective treatment for gastric superficial lesions, without compromising cancer survival. Endoscopic resection should also be considered as first-line treatment for gastric neoplasias in Western countries.